REPRESENTASI OTHERNESS DAN DISKRIMINASI GENDER SERIAL BLUE EYE SAMURAI: ANALISIS SEMIOTIKA JOHN FISKE - Dwi Risqi Maulana; Teguh Hartono Patriantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the representation of otherness and gender discrimination in the series Blue Eye Samurai using John Fiske’s semiotic analysis. Employing a qualitative descriptive approach, the research examines three levels of meaning: reality, representation, and ideology. The findings reveal that Mizu faces racial discrimination due to her mixed heritage, symbolizing Japan’s obsession with racial purity, while Akemi experiences gender oppression under patriarchal control as a political instrument. Through visual symbols, dialogue, and narrative structure, the series critiques social systems that marginalize difference and female autonomy